Eksistensi Bank Wakaf Mikro Dan Implikasinya Terhadap Kesejahteraan Masyarakat Dalam Perspektif Islam - Yusvita Nena Arinta; Rifda Nabila; Ahmad Ulil Albab Al Umar; Anita Wahyu Alviani; Yuni Inawati (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to analyze the existence of micro waqf banks and their implications for public welfare in an Islamic perspective. This research is an empirical study with qualitative. The data in this study are secondary data obtained from various journal, book and internet sources. The results in this study showed that Micro Waqf Bank is present as a funding solution in the community and it is proved able to guarantee the welfare of the community without contradicting the Islamic law.